Robusta Coffee (Coffeacanephora) Decreasing IL-1Î± (Interleukin-1Î±) Expression and Increasing the Number of Fibroblasts in Healing Process in Dental Pulp in Wistar Rats - I Dewa Ayu Ratna Dewanti; I Dewa Ayu Susilawati; Pujiana Endah Lestari; Ristya Widi Endah Lestari; Erawati Wulandari; Roedy Budirahardjo; Dyah Setyorini; Sunlip Wibisono (Institute for Research and Community Services (LPPM) ITB, 2019)
Fibroblasts and IL-1Î± are important components of inflammation and healing in dental caries. This healing allegedly could be enhanced by robusta coffee. The aim of this study was to investigate the effect of varying concentrations of robusta coffee on IL-1Î± expression and the number of fibroblasts. Wistar rats were used, divided into 4 groups and 3 subgroups (7-, 14